Colostomy closure in post Conflict Iraq - Al-Khaldy,NajimA.I.; Al-Hashimi, Ali S.; Abd Ali, Mardukh S. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Colostomy minimizes the risk of leakage at expense of requiring a second operation. In Iraq, published on colostomy closure in penetrating abdominal wall injuries is scarce. Objective: to Study the prognosis of colostomy closure in post-conflict patients in Iraq. J Fac Med Baghdad 2018; Vol.60, No.3 Received: June, 2018 Accepted: Oct., 2018 Published: Dec.2018 Method: This is a retrospective study of 52 patients subjected to colostomy closure, recruited for the period 2008 to 2009 from Al-Yarmouk Teaching Hospital and Children Central Teaching Hospital. Demographic data and information about colostomy (type, methods of preparation … etc.) were studied. Results: Trauma was noticed in 57.7% patients. Transverse colon was the commonest site of injuries. The complications were wound infection (19.2%), fecal fistula (3.8%), anastomotic leak (1.9%) and abdominal abscess (1.9%). A significant high complication rate was associated with conventional method of preparation, and double layer anastomosis (p = 0.004 rand 0.003, respectively). Conclusion: the finding were comparable with other centers in the world.